Influence of job demand, social support and perfectionism on presenteeism among employees in Hospitality industry: the mediating role of job burnout - Chong, Chin Ann (2022)
The purpose of this study is to investigate the influence of job demand, social support and perfectionism on presenteeism. Thus far, studies on the mediating mechanism of job burnout between perfectionism and presenteeism remain scant. Besides, this research provides a more holistic view by examining the extent to which job demands (workload, time pressure, job insecurity) and social support explain the tendency of presenteeism among employees directly and indirectly via job burnout in the context of hospitality industry in Malaysia. This study adopted a quantitative and deductive research approach with a cross-sectional study design was applied. The main target of this study is the hospitality workers located in Perak, Kuala Lumpur, and Selangor. As sampling frame is not available, this study employed a non-probability sampling technique (i.e., snowball sampling). G*Power was used to determine the study's minimal sample size of 215. A total of 220 completed self-administered questionnaires were returned by the hospitality employees who participated in this study. SPSS version 26 was used for data entry and descriptive analysis, whereas SmartPLS 3.0 was employed to test the hypotheses. The results demonstrated that job insecurity and time pressure positively influenced job burnout. Job insecurity is the main cause of job burnout. Perfectionism contributes to job burnout. However, social support and workload were found to have no effect on employees’ job burnout. On the other hand, job burnout and perfectionism have a positive influence on presenteeism. Job insecurity, as well as social support, have a negative substantial influence on presenteeism. Workload and time pressure have no effect on presenteeism. Finally, job burnout mediates the relationship between time pressure and job insecurity on presenteeism among employees. The influence of workload, social support, and perfectionism on presenteeism was not mediated by job burnout. This study adds to the current knowledge by analyzing the influence of job burnout in reducing presenteeism in Malaysian hospitality industry. Moreover, management, human resource workers, and societies can help reduce presenteeism-related burnout.